The media and communication dictionary a guide for students, educators, and professionals - Kleinman, Sharon (Peter Lang, 2011)
Suitable for students, educators, and professionals in the field of media and communication, this title is designed to help readers understand the developments in our media-rich environment as well as fundamental and historically significant terms and concepts.